Rates and Trends of Endotracheal Intubation in Patients With Status Epilepticus. (October 2019) - Alkhachroum, Ayham M.; Rubinos, Clio; Chatterjee, Abhinaba; Chen, Monica L.; Martin, Andrew; Claassen, Jan; Murthy, Santosh B.; Merkler, Alexander E.
Objective: Among patients with status epilepticus, we sought to determine the rate of endotracheal intubation, identify the physician specialties responsible for endotracheal intubation, and characterize the trend in use of endotracheal intubation over the last 20 years. Methods: We performed a cross-sectional study using data from 2 sources. First, we used inpatient claims between 2009 and 2015 from a nationally representative 5% sample of Medicare beneficiaries. Patients with status epilepticus were identified using International Classification of Diseases, 9th Revision, Clinical Modification ( ICD-9-CM ) codes, and those who underwent endotracheal intubation were identified based on Current Procedural Terminology codes. Medical specialties of providers performing intubation were identified based on Healthcare Provider Taxonomy Codes. Second, we used claims data from the National Inpatient Sample (NIS) to estimate the annual rates and trends of endotracheal intubation and tracheostomy among patients with status epilepticus from 1995 to 2014. Results: Among 1971 Medicare beneficiaries with status epilepticus, 566 (29%) patients underwent endotracheal intubation. 375 (66%) patients were intubated on admission. The most common medical providers performing intubation in patients with status epilepticus were emergency medicine physicians (50.4%), anesthesiologists (16.4%), and pulmonary medicine physicians (10.1%). Neurologists accounted for 1.7% of all intubations. Among individuals with status epilepticus identified in the NIS, 248 681 (41.7%) were intubated. The proportion of patients intubated increased from 29.5% (95% confidence interval [CI]: 27.8%-31.3%, P = .018) in 1995 to 50.8% (95% CI: 49.6%-52%, P = .012) in 2014. The proportion of patients with status epilepticus who underwent tracheostomy increased from 2.2% (95% CI: 1.7%-2.7%, P = .005) in 1995 to 3.4% (95% CI: 3%-3.9%, P = .004) in 2014. Significance: Approximately 1 in 3 patients with status epilepticus undergo endotracheal intubation. Over the last 20 years, the proportion of patients with status epilepticus undergoing endotracheal intubation has almost doubled. Neurologists perform a small percentage of these intubations.